The Prevalence of Pks Genotoxin Among Klebsiella Pneumoniae Isolated from Different Clinical Samples in Baghdad, Iraq - Mohammed, Mustafa Jasim; Mahmood, Suhad Saad (Iraqi Journal of Science, 2024)
Klebsiella pneumoniae is a pathogenic bacterium that has been linked to several illnesses acquired in both the community and hospitals. This study aimed to determine the prevalence of the clbA, K1, and K2 genes in K. pneumoniae and their relationship with antibiotic resistance. In this research, 130 clinical samples from patients in hospitals were collected from blood, urine, wounds, burns, and sputum, and only 61 of those samples were positively identified as K. pneumoniae using biochemical tests, selective media, and Vitek II. The method of disc diffusion was utilized to evaluate the 61 isolates' susceptibility to 10 antibiotics, including Imipenem, Meropenem, Cefixime, Ceftazidime, Amoxicillin-clavulanate, Gentamicin, Aztreonam, Azithromycin, Levofloxacin, and Trimethoprim-sulfamethoxazole. The results showed that the highest resistance was towards amoxicillin-clavulanate (98.36%) and the lowest towards meropenem (13.11%), and that 95.08% of the isolates were multidrug resistant (MDR). The clbA, K1, and K2 genes were detected using conventional PCR; the results showed that out of 61 isolates, only 3 were positive for K1, 52 were positive for K2, and none of the isolates were clbA+. (2/3) of the K1 and (51/52) of the K2 isolates were MDR. The finding shows a substantial association between the K1 and K2 genes and resistance to antibiotics, as the capsule is the main virulence factor in this bacteria.